Screening asylum seekers in Denmark for torture using a structured questionnaire - Munk-Andersen, Ebbe; Toftgaard, Bettina; Modvig, Jens (Torture Journal, 2021)
The United Nations Committee against Torture recommends systematic torture screening throughout the asylum process. The goal of this study is to evaluate the introduction of a structured questionnaire, coding for torture according to the definition from United Nations Convention Against Torture (UNCAT). This screening for torture is now an integrated part of the medical reception of newly arrived asylum seekers The screening was carried through during a 2 years period as a part of the routine health screening, and alleged torture victims were referred to further medical examination and offered assistance to carry information about the torture to the Immigration Service. The participation rate was 85.2%, and torture was reported among 27.8% of the males, with a mean of 21.2% among both sexes. Key words: Torture, screening, questionnaire, asylum seekers, UNCAT